Hydatid Cyst Migration in Peritoneal Cavity: A Case Report - Markov, Petar; Milev, Ilija; Mitevski, Aleksandar (Lietuvos chirurgija, 2019)
Introduction. Cystic echinococcosis is a zoonosis caused by the larval stage of Echinococcus granulosus. In most of cases hydatid cysts are found in the liver but in rare cases a migration of the hydatid cyst can occur following rupture of hepatal pericist.Case. A 38 year old female presented with abdominal pain, fatigue, weakness and fever for more than three months. Computed tomography show segment II and IV hepatic per-magna cystic formations with dimensions: No I: 80×60×74 mm and No. II: 70×60×58 mm. Per magna cystic formation in the Douglas space, with dimensions of 93×90×62 mm with clearly expressed mass effect on surrounding organ structures.Discussion. Active hydatid disease may show migration of cysts due to rupture of hepatal pericyst, pressure difference between the anatomic cavities, and by contribution of gravity. Sudden death, anaphylactic shock and dissemination of disease can be seen with cystic content spillage into the peritoneal cavity.Conclusion. Migrated hydatid cysts are very rare parasitic manifestation presenting with symptoms deriving from the neighboring organs. They are diagnosed typically by CT and managed with evacuation of cysts following abdominal exploration. Full abdominal organ ultrasonography, with accent on the liver, should be performed in any case of intraabdominal simple cyst presence.
Keywords: hydatid; cyst; rupture; migration